The Fly Sensitizing Pigment Enhances UV Spectral Sensitivity While Preventing Polarization-Induced Artifacts - Ilić, Marko; Meglič, Andrej; Kreft, Marko; Belušič, Gregor (Frontiers in Cellular Neuroscience, 2018)
Microvillar photoreceptors are intrinsically capable of detecting the orientation of e-vector of linearly polarized light. They provide most invertebrates with an additional sensory channel to detect important features of their visual environment. However, polarization sensitivity (PS) of photoreceptors may lead to the detection of polarization-induced false colors and intensity contrasts. Most insect photoreceptors are thus adapted to have minimal PS. Flies have twisted rhabdomeres with microvilli rotated along the length of the ommatidia to reduce PS. The additional UV-absorbing sensitizing pigment on their opsin minimizes PS in the ultraviolet. We recorded voltage from Drosophila photoreceptors R1-6 to measure the spectral dependence of PS and found that PS in the UV is invariably negligible but can be substantial above 400 nm. Using modelling, we demonstrate that in R1-6 without the sensitizing pigment, PS in the UV (PSUV) would exceed PS in the visible part of the spectrum (PSVIS) by a factor PSUV/PSVIS=1.2-1.8, as lower absorption of Rh1 rhodopsin reduces self-screening. We use polarimetric imaging of objects relevant to fly polarization vision to show that their degree of polarization outdoors is highest in the short-wavelength part of the spectrum. Thus, under natural illumination, the sensitizing pigment in R1-6 renders even those cells with high PS in the visible part unsuitable for proper polarization vision. We assume that fly ventral polarization vision can be mediated by R7 alone, with R1-6 serving as an unpolarized reference channel.